Effects of the administration of a bolus of 7,2% hypertonic saline solution in horses with colic, as a part of medical treatment : a preliminary study - Stilwell, Catarina Campos de Carvalho (2017)
Dissertação de Mestrado Integrado em Medicina Veterinária